INDONESIAN COMPANIES LEARNING CULTURE ANALYSIS IN INDUSTRIAL ERA 4.0 - Silvianita, Anita (Dinasti Publisher, 2020)
Business competition in the current industrial era 4.0 requires each company to have a strategy in managing their company to be able to survive and compete with other companies, as well as in Indonesia. In connection with the industry 4.0 era, companies need to consider the importance of a culture of learning within the company, so that the work process runs more smoothly. They have to provide some facilities in order to support the learning process for their employees. In addition, employees must have the initiative to learn how the information and technology revolution can improve performance in order to be able to increase the country's net exports. The purpose of this study is to identify how the culture of learning in companies, especially in Indonesia. In addition, through this research also proposes a learning culture that is appropriate to the industrial era 4.0 in Indonesia.